Increased risk of incident heart failure and death is associated with insulin resistance in people with newly diagnosed type 2 diabetes: UKPDS 89 - Wamil, M; Coleman, RL; Adler, AI; McMurray, JJV; Holman, RR (American Diabetes Association, 2021)
OBJECTIVE Insulin resistance (IR) may mediate heart failure (HF) development. We examined whether IR in people with newly diagnosed type 2 diabetes (T2D) increased their risk of a composite outcome of HF or death or of HF alone.